A viable secondary intra-abdominal pregnancy resulting from rupture of uterine scar: role of MRI - Teng, H.C.; Kumar, G.; Ramli, N.M. (British Institute of Radiology, 2007)
Pre-natal diagnosis of intra-abdominal pregnancy is difficult. Ultrasound has been the frontline modality to date; however, it gives a diagnostic error of 50-90% and its use is disappointing. In recent years, MRI has emerged as an appealing imaging modality. With its good soft tissue contrast and non-ionizing property, it acts as a means of definitive non-invasive assessment before surgical intervention when ultrasound is inconclusive.